Instruments of accelerated socio-economic development of the subjects of the Russian Federation - R. M. Koshmidov (Вестник Северо-Кавказского федерального университета)
The article studies individual instruments of stimulating the accelerated development of the subjects of the Russian Federation. It has been established that among these tools the individual programs of socioeconomic development of the subjects of the Russian Federation are aimed to the greatest extent at reducing inter-regional inequality by stimulating the accelerated development of the most lagging regions. In this regard, the specifics of individual programs are considered in detail, and the directions of their improvement are proposed.